Luminescent diamond composites. Issue 1 (31st December 2022) - Sedov, Vadim; Kuznetsov, Sergei; Martyanov, Artem; Ralchenko, Victor
Abstract: Diamond is valuable material with extraordinary high thermal conductivity and transparency in a wide spectral range from UV to IR and longer wavelengths. Defects and impurities in the diamond lattice can absorb and emit light at wavelengths specific for each of such "color centers." Particularly, the vacancy-related defects in diamond, such as nitrogen-vacancy (NV) or silicon-vacancy (SiV) centers, are actively investigated due to their potential for biomedicine, quantum optics, local thermometry and magnetometry. Although a great variety of different color centers in diamond are discovered, only a limited number of those point defects can be reliably reproduced in synthetic diamond, obtained either by chemical vapor deposition (CVD) or high-pressure high-temperature (HPHT). An alternative approach to producing luminescent diamond-based materials is to integrate stable non-diamond sources of luminescence in the form of nano- or microparticles of foreign materials into the pristine diamond. The produced diamond composites possess excellent properties of diamond combined with optical emission characteristics, which cannot be provided with intrinsic defects in diamond. The good candidates for the materials of such impurities are well-investigated fluorides and oxides doped by rare-earth elements (RE) or other luminescent chalcogenides such as sulfides, selenides and tellurides. Here we briefly review recent achievements in fabrication and properties of these new luminescent diamond-RE composites, compare them with luminescent properties of doped diamond, and outline prospects for applications of the luminescent diamond composites for photonics, markers, monitors of high-power synchrotron, X-ray beams and X-ray lasers.